“A Study on consumer buying behaviour of baby care products in Navi Mumbai area” (International Journal of Food and Nutritional Sciences, 2022)
This research delves into the intricate dynamics of consumer behaviour concerning baby care products within the Navi Mumbai area, emphasizing the pivotal roles of brand consciousness and perceived product quality. Through a quantitative approach, this study investigates parental preferences and decision-making processes when purchasing baby care items. Hypotheses cantered on brand consciousness and perceived quality were scrutinized through Likert-based questionnaires distributed among 443 respondents. The findings reveal a substantial inclination toward established brands driven by trust, endorsements, and familiarity, underscoring the criticality of brand reputation in consumer decision-making. Moreover, the study illuminates the paramount influence of perceived product quality on buying behaviour, elucidating the significance of quality attributes, reliability, and satisfaction in consumer choices.